Answer:
ndkndksndssjsjsjsjsjs nsj
Step-by-step explanation:
Answer:
a) y = |x/2 -2| +4
b) y = |x/2 -2| +2
c) y = |(x+1)/2 -2| +3
d) y = |(x-1)/2 -2| +3
Step-by-step explanation:
To translate the function f(x) by (h, k) in the (right, up) direction, you transform it to ...
g(x) = f(x -h) +k
<u>a) one unit up</u>
Add 1 to the function value.
![y=\left|\dfrac{x}{2}-2\right|+3+1\\\\\boxed{y=\left|\dfrac{x}{2}-2\right|+4}](https://tex.z-dn.net/?f=y%3D%5Cleft%7C%5Cdfrac%7Bx%7D%7B2%7D-2%5Cright%7C%2B3%2B1%5C%5C%5C%5C%5Cboxed%7By%3D%5Cleft%7C%5Cdfrac%7Bx%7D%7B2%7D-2%5Cright%7C%2B4%7D)
<u>b) one unit down</u>
Subtract 1 from the function value.
![y=\left|\dfrac{x}{2}-2\right|+3-1\\\\\boxed{y=\left|\dfrac{x}{2}-2\right|+2}](https://tex.z-dn.net/?f=y%3D%5Cleft%7C%5Cdfrac%7Bx%7D%7B2%7D-2%5Cright%7C%2B3-1%5C%5C%5C%5C%5Cboxed%7By%3D%5Cleft%7C%5Cdfrac%7Bx%7D%7B2%7D-2%5Cright%7C%2B2%7D)
<u>c) one unit left</u>
Replace x with x-(-1).
![y=\left|\dfrac{x-(-1)}{2}-2\right|+3\\\\\boxed{y=\left|\dfrac{x+1}{2}-2\right|+3}](https://tex.z-dn.net/?f=y%3D%5Cleft%7C%5Cdfrac%7Bx-%28-1%29%7D%7B2%7D-2%5Cright%7C%2B3%5C%5C%5C%5C%5Cboxed%7By%3D%5Cleft%7C%5Cdfrac%7Bx%2B1%7D%7B2%7D-2%5Cright%7C%2B3%7D)
<u>d) one unit right</u>
Replace x with x-1.
![\boxed{y=\left|\dfrac{x-1}{2}-2\right|+3}](https://tex.z-dn.net/?f=%5Cboxed%7By%3D%5Cleft%7C%5Cdfrac%7Bx-1%7D%7B2%7D-2%5Cright%7C%2B3%7D)
Answer:
Between 7 and 14
Step-by-step explanation:
Answer:
62
Step-by-step explanation:
90 - 28
complementary angles equal to 90